Antibacterial and Antifungal Activity of Sida cordifolia Linn. - PRABHAKAR, T.; NAGARATHNA, P.K.M.; SRINIVAS RAO, T.; BABY, BENY; RAMESH, K.; SURESH, B. (Asian Journal of Chemistry, 2010)
The antibacterial and antifungal activity of chloroform and methanol extract of leaves and roots of the plant Sida cordifolia Linn. was studied. The results of study revealed that the chloroform and methanol extracts of leaves, roots of the plant exhibited significant activity against B. subtilis, S. aureus, B. cerius, and C. albicans. The other organisms P. vulgaris, A. niger, A. fumigants, exhibited moderate susceptibility.